2016
DOI: 10.1534/genetics.116.190314
|View full text |Cite
|
Sign up to set email alerts
|

A Parthenogenesis Gene Candidate and Evidence for Segmental Allopolyploidy in Apomictic Brachiaria decumbens

Abstract: Apomixis, asexual reproduction through seed, enables breeders to identify and faithfully propagate superior heterozygous genotypes by seed without the disadvantages of vegetative propagation or the expense and complexity of hybrid seed production. The availability of new tools such as genotyping by sequencing and bioinformatics pipelines for species lacking reference genomes now makes the construction of dense maps possible in apomictic species, despite complications including polyploidy, multisomic inheritanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 64 publications
(103 reference statements)
8
81
0
1
Order By: Relevance
“…Conclusive evidence of segmental allopolyploidy was recently documented in a tetraploid apomictic accession of B. decumbens (CIAT 606, cv. Basilisk) (Worthington et al, 2016). The admixture with B. brizantha observed in the tetraploid apomictic B. decumbens accessions in the STRUCTURE analysis suggests that one subgenome of B. decumbens may be closely related to B. ruziziensis , whereas the other is more similar to B. brizantha .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conclusive evidence of segmental allopolyploidy was recently documented in a tetraploid apomictic accession of B. decumbens (CIAT 606, cv. Basilisk) (Worthington et al, 2016). The admixture with B. brizantha observed in the tetraploid apomictic B. decumbens accessions in the STRUCTURE analysis suggests that one subgenome of B. decumbens may be closely related to B. ruziziensis , whereas the other is more similar to B. brizantha .…”
Section: Discussionmentioning
confidence: 99%
“…CIAT 26179 was classified as an apomictic tetraploid accession of B. brizantha in the EMBRAPA genebank, and this assignment was subsequently confirmed by studies of reproductive mode (Vigna et al, 2011) and chromosome counts (Mendes‐Bonato et al, 2002). However, CIAT 26179 is listed as B. ruziziensis in the CIAT genetic resources database and was classified as sexually reproducing by the diagnostic apomixis marker p779/p780 (Worthington et al, 2016). Similarly, the B. decumbens accession CIAT 26186 was classified as sexually reproducing by marker analysis with p779/p780 but was described as a tetraploid apomict by EMBRAPA (Penteado et al, 2000; Valle et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study revealed that the PsASGR-BBML gene, which is in perfect linkage with the ASGR of both Pennisetum and Cenchrus , could induce parthenogenesis or the initiation of embryo development from an unfertilised egg cell38. ASGR-BBML was strongly supported as a candidate gene for the apomictic function of parthenogenesis60. In contrast to their function at the stage of parthenogenesis in Pennisetum, AP2 genes are expected to have important functions in diplosporous development in B. tricuspis .…”
Section: Discussionmentioning
confidence: 99%
“…This would combine the advantages of true seed production while avoiding the numerous disadvantages of vegetative clones as already discussed. Apomixis has been shown to be under genetic control in multiple species (reviewed in (Bicknell and Catanach, 2015)), with a number of recent genetic mapping studies in tropical polyploid forage grasses such as the tetraploid Brachiaria decumbens or the hexaploid Urochloa humidicola revealing major QTL underlying the trait (Vigna et al, 2016;Worthington et al, 2016). A nice example of where apomixis is actively used in polyploid breeding is in Kentucky bluegrass (Poa pratensis) (Huff, 2010).…”
Section: Where Next For Polysomic Polyploid Breeding?mentioning
confidence: 99%